Dětství v životopisných textech švédských Romů - tendence a proměny - Zahova, Sofiya (Romano džaniben, 2017)
The article discusses narratives about Romani childhood in several books published in Sweden by Roma or as a result of cooperation between a Romani personality and a professional writer, particularly the children literature writer Gunilla Lundgren. These works are mainly first-person narratives and are based on accounts of the Romani personality’s own and his/her family life. The narrative is usually accompanied by visual material: photographs, pictures and graphics. Some of the main works written by or about Kalderash Roma will be discussed with view of childhood (re)presentations/accounts in them. The aim is to analyse tendencies and changes in the way these texts narrate Romani childhood over time. The works will be discussed in a chronological perspective, with reflections on the impact of the historical and social context of Swedish and international Romani politics.